2020
DOI: 10.1016/j.xcrm.2020.100121
|View full text |Cite
|
Sign up to set email alerts
|

Oral SARS-CoV-2 Inoculation Establishes Subclinical Respiratory Infection with Virus Shedding in Golden Syrian Hamsters

Abstract: Summary Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) is transmitted largely by respiratory droplets or airborne aerosols. Despite being frequently found in the immediate environment and feces of patients, evidence supporting the oral acquisition of SARS-CoV-2 is unavailable. Using the Syrian hamster model, we demonstrate that the severity of pneumonia induced by the intranasal inhalation of SARS-CoV-2 increases with virus inoculum. SARS-CoV-2 retains its infectivity in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(163 citation statements)
references
References 30 publications
11
150
2
Order By: Relevance
“…Further, a decrease in body mass had been reported in the initial phase of SARS-CoV2 infection. Inline, intranasal SARS-CoV2 infection in GSH showed a gradual body mass loss peaking (~10% as compared to uninfected) at 4 dpi with 10 4 and 10 5 plaque-forming unit (PFU) ( Figure 2A ) (Chan et al, 2020; Imai et al, 2020; Lee et al, 2020; Sia et al, 2020). This was accompanied by gross lung morphological changes characterized by pneumonitis regions with a high viral dose 10 5 (PFU).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Further, a decrease in body mass had been reported in the initial phase of SARS-CoV2 infection. Inline, intranasal SARS-CoV2 infection in GSH showed a gradual body mass loss peaking (~10% as compared to uninfected) at 4 dpi with 10 4 and 10 5 plaque-forming unit (PFU) ( Figure 2A ) (Chan et al, 2020; Imai et al, 2020; Lee et al, 2020; Sia et al, 2020). This was accompanied by gross lung morphological changes characterized by pneumonitis regions with a high viral dose 10 5 (PFU).…”
Section: Resultsmentioning
confidence: 94%
“…SARS-CoV2 is inefficient in infecting mice due to structural differences in mouse ACE2 as compared to human ACE2, thus wild type mice are not the natural host to study SARS-CoV2 induced pathologies (Bao et al, 2020, p. 2; Chan et al, 2020). On the other hand, GSH, which was previously described as a model for SARS-CoV infection, has recently gained much attention as a suitable model for studying SARS-CoV2 infection (Chan et al, 2020; Imai et al, 2020; Kaptein et al, 2020; Kreye et al, 2020; Lee et al, 2020; Osterrieder et al, 2020; Sia et al, 2020; Tostanoski et al, 2020). Remarkably, hamsters have been shown to be infected through intranasal, oral and ophthalmic routes by SARS-CoV2 with respectively descending lung viral load and pathologies (Imai et al, 2020; Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACE2 was also reported on the epithelial cells of the oral mucosa ( 90 ). Using a Syrian Hamster animal model of SARS-CoV-2 infection, it was recently reported that oral inoculation of SARS-CoV-2 established mild pneumonia in 67% of animals exposed to the virus and caused intestinal inflammation ( 91 ). The expression of ACE2 on enterocytes of the small intestine was reported by Hamming et al ( 88 ), with the highest expression found in the brush border of intestinal enterocytes ( 92 , 93 ), the main role of which is to ensure the absorption of nutrients.…”
Section: Tissue Distribution Of the Ace2 Viral Receptor And Sars-cov-mentioning
confidence: 99%
“…Moreover, persistent fecal viral shedding has been observed in pediatric patients ( Xu et al, 2020a , b ) and there is evidence that SARS-CoV-2 can replicate productively in human enteroids and enterocytes ( Lamers et al, 2020 ; Zhou et al, 2020 ). More recently, it was demonstrated that multi-route mucosal inoculation (including oral inoculation) of African green monkeys with SARS-CoV-2 results in infection in both the respiratory and gastrointestinal tract ( Hartman et al, 2020 ), and orally inoculated golden Syrian hamsters develop respiratory and intestinal infection ( Chak-Yiu Lee, et al 2020 ). Collectively, these observations suggest that fecal-oral transmission of SARS-CoV-2 is possible.…”
Section: Introductionmentioning
confidence: 99%